DISCOVERY OF AN UNKNOWN FLUORESCENT URANIUM-CONTAINING MINERAL IN THE ROCKS OF MOUNT BULL - D. A. Tsebro; D. V. Shchitov; P. A. Sidyakin (Современная наука и инновации, 2022)
In view of the presence of a rich chemical environment on the surface and in the underground part of the CMW laccolith mountains, the complex structure of mountain ranges (cracks, cavities, adits and shafts), the processes of radon transfer by air masses and high humidity, special conditions are formed that contribute to the formation of new mineralizations in a period of 20-50 years. According to the results of geological exploration work on Mount Byk, among six mineral samples a new mineral has been discovered and confirmed. The chemical formula is similar to strassmanite, but it is new to our region and has a unique crystal structure different from other minerals.